Sustainable development and natural resource accounting in a small open economy: a methodological clarification - Gómez-Lobo, Andrés (Estudios de Economía, 2016)
The effort to correct the national accounts in order calculate NNP or related ‘Green GDP’ concepts, known as natural resources accounting, has been a lively research area in the last decade. Two basic methodologies have been proposed in the literature to value the loss of natural assets, the net price or depreciation method and the user cost approach. This paper aims to show that the user cost approach is incorrect and misleading.In arguing for its use, its original proponent implicitly had the context of a small open economy in mind. However, in this context, the depreciation method is somewhat different from its closed economy counterpart. In a small open economy, to arrive at a sustainable NNP figure changes in foreign assets must also be accounted for. Once this is done, the main criticism to the depreciation method –that resource rich countries would not have a consumption advantage over resource poor countries – can be shown to be wrong. For this and other reasons it is recommended that only the depreciation method be used in resource accounting methodologies. As a secondary result, this paper stresses the importance of incorporating changes in foreign assets in applied work on resource accounting in small developing countries.